Chromatographic capture of cells to achieve single stage clarification in recombinant protein purification. (8th December 2021) - Almeida, Aaron; Chau, David; Coolidge, Thomas; El‐Sabbahy, Hani; Hager, Steven; Jose, Kevin; Nakamura, Masa; Voloshin, Alexei
Abstract: Recent advancements in cell culture engineering have allowed drug manufacturers to achieve higher productivity by driving higher product titers through cell line engineering and high‐cell densities. However, these advancements have shifted the burden to clarification and downstream processing where the difficulties now revolve around removing higher levels of process‐ and product‐related impurities. As a result, a lot of research efforts have turned to developing new approaches and technologies or process optimization to still deliver high quality biological products while controlling cost of goods. Here, we explored the impact of a novel single use technology employing chromatographic principle‐based clarification for a process‐intensified cell line technology. In this study, a 16% economic benefit (/g) was observed using a single‐use chromatographic clarification compared to traditional single‐use clarification technology by improving the overall product cost through decreased operational complexity, higher loading capacity, increased product recovery, and higher impurity clearance. In the end, the described novel chromatographic approach significantly simplified and enhanced the cell culture fluid harvest unit operation by combining the reduction of insoluble and key soluble contaminants of the harvest fluid into a single stage.